Analisis Pengaruh Iklim Keselamatan terhadap Keselamatan Pelayaran pada Perusahaan Pelayaran Kapal Penumpang di Surabaya - Djamaludin Malik; Wisnoe Widodo; Mudiyanto, Mudiyanto; Rizky, Syabania B. (Lembaga Penelitian dan Pengabdian Masyarakat, Akademi Maritim Nusantara Cilacap, 2023)
This study examines the effect of safety climate on shipping safety. The purpose of this study was to analyze the influence of the passenger ship safety climate on shipping safety. This study used a questionnaire as a data collection instrument with non-probability sampling techniques at the Port of Tanjung Perak Surabaya and 100 respondents who participated in this study. The inferential statistical method used in the analysis of research data is Partial Least Square (PLS). Instrument reliability is acceptable with Cronbach alpha values and composite reliability values above 0.70. The results of hypothesis testing in this study are that the safety climate has a significant effect on shipping safety. This means that to achieve shipping safety, the safety climate needs to be considered in indicators of safety procedures, communication and safety involvement of the crew. The conclusion of this study is that the safety climate in implementing the ISM Code promotes and disseminates a culture of safety, especially shipping safety on passenger ships.